2019
DOI: 10.26502/fccm.92920094
|View full text |Cite
|
Sign up to set email alerts
|

ECG Changes and Their Prognostic Impact in Patients With Takotsubo Syndrome

Abstract: Aim: Within this study, we investigated ECG changes in acute patients diagnosed with Tako Tsubo syndrome (TTS) and report on the prognostic impact of the respective ECG patterns. Methods and Results: This single-center study included 101 consecutive patients diagnosed with TTS between 2006 and 2017. Upon 12-lead admission ECG, 59 patients had ST-segment elevation (58%, STEMI), 9 patients had only ST-segment depression (9%, NSTEMI) and 27 T-wave inversion (27%, NSTEMI). Patients who were admitted to the hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…However, in the last years, studies showed that TTS may cause multiple fatal complications, resulting in in‐hospital mortality between 1% and 8%. 4 , 35 , 36 , 37 , 38 In agreement with previously published studies, the all‐cause in‐hospital mortality in our study was 2.3% in period 1 and 2.8% in period 2. Moreover, there was no difference in in‐hospital and 30‐day all‐cause mortality between the two periods.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, in the last years, studies showed that TTS may cause multiple fatal complications, resulting in in‐hospital mortality between 1% and 8%. 4 , 35 , 36 , 37 , 38 In agreement with previously published studies, the all‐cause in‐hospital mortality in our study was 2.3% in period 1 and 2.8% in period 2. Moreover, there was no difference in in‐hospital and 30‐day all‐cause mortality between the two periods.…”
Section: Discussionsupporting
confidence: 93%
“…Because of the complete recovery of the left ventricle function, TTS was initially considered a benign condition. However, in the last years, studies showed that TTS may cause multiple fatal complications, resulting in in‐hospital mortality between 1% and 8% 4,35–38 . In agreement with previously published studies, the all‐cause in‐hospital mortality in our study was 2.3% in period 1 and 2.8% in period 2.…”
Section: Discussionsupporting
confidence: 92%